Functions and roles of representative bodies in the state administration system (critical analysis of the journey of democracy in Indonesia) - Busroh, Firman Freaddy (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The purpose of this study is to determine the function and role of representative bodies in the Indonesian constitutional system by looking at the journey of democracy in Indonesia. This research uses a descriptive qualitative research method based on a literature study and a normative law approach. The data in this study is secondary data obtained by observing literature. The results of this study indicate that basically, the DPD, DPR, and DPRD have the same functions and roles, namely the function of legislation, the function of budgeting, and the function of supervision. The difference between the three lies in the representation that is shaded and the details of the duties and authorities that emerge from these functions. The DPD only appeared after the third amendment to the 1945 Constitution. The DPR has existed since the Dutch colonial era, although it was abolished during the Japanese colonial period. This study concludes that the fact that there is a representative council in Indonesian democracy is something that has a vital role.